Cooperative Institutional Research Program (CIRP) (United States): Freshman Survey, 1973 ([Verlag nicht ermittelbar], 2002)
The principal purposes of this national longitudinal study of the higher education system in the United States are to describe the characteristics of new college freshmen and to explore the effects of college on students. For each wave of this survey, each student completes a questionnaire during freshman orientation or registration that asks for information on academic skills and preparation, high school activities and experiences, educational and career plans, majors and careers, student values, and financing college. Other questions elicit demographic information, including sex, age, parental education and occupation, household income, race, religious preference, and state of birth. Specific questions asked of respondents in the 1973 survey included student status (full- or part-time), factors influencing students' decision to attend a particular college, and general information about the students' parents. Respondents were also asked to list their probable career choice, first, second, and least appealing choice of major field of study, and activities they engaged in during their previous year in school. Also elicited were respondents' opinions on the importance of various individuals and events in their decision to enroll in college, assessments of achieving certain goals during their college years, and general attitudes about faculty and other students.